Orbital Surgery: Evolution and Revolution - Newman, Steven A. (Journal of Neurological Surgery Part B: Skull Base, 2021)
This article traces the development of orbital surgery and its subsequent modifications. It also points out the importance of defining one’s goal before embarking on orbital surgery. Although generally considered part of ophthalmology, surgery on the orbit has been relatively neglected and not routinely practiced. This article reviews the history of development of orbital surgery, both the revolutionary ideas and the evolutionary changes. There are multiple orbital lesions that do not need to be treated with surgery at all. These days chemotherapy, radation therapy, or even immunotherapy may be more appropriate. The most common orbital pathology, that is thyroid orbitopathy, the physician needs to decide whether or not the orbit needs to be decompressed or whether there are problems related to motility that can be dealt with by eye muscle surgery.
Keywords: orbitototomy; fine needle aspiration biopsy; computerized axial topography; transconjunctival incisions; Krönlein's orbitotomy; orbital deconstruction